1990
DOI: 10.1080/00150199008008907
|View full text |Cite
|
Sign up to set email alerts
|

Determined exoelectron emission effect in doped TGS

Abstract: The exoelectron emission from AD TG SP crystals has been investigated under pyroelectric effect con ditions. It has been established that in doped crystals there is observed a reproducible emission effect. An equation for the depolarizing field determining the exoemission current has been derived. It is shown that in crystals with fixed domain structure near the Curie point the emission kinetics is limited by the temperature behaviour of the ratio y /z (where 7 is the pyroelectric coefficient, e is the dielect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Measurements of FEE and the dependence of ␥/ implemented for highly doped TGS with immobile domain structure, demonstrated that the FEE current behavior is similar to the temperature dependence of the parameter ␥/. 57 Recently, comparative studies of several ferroelectric crystals and ferroelectric PLZT ceramics were implemented by Shur and Rosenman. 58 PLZT ceramic samples and undoped monodomain LiNbO 3 , TGS, Gd 2 ͑MoO 4 ͒ 3 , and Pb 5 Ge 3 O 11 crystals were studied in the experiments.…”
Section: Fee During Phase Transitionsmentioning
confidence: 94%
See 3 more Smart Citations
“…Measurements of FEE and the dependence of ␥/ implemented for highly doped TGS with immobile domain structure, demonstrated that the FEE current behavior is similar to the temperature dependence of the parameter ␥/. 57 Recently, comparative studies of several ferroelectric crystals and ferroelectric PLZT ceramics were implemented by Shur and Rosenman. 58 PLZT ceramic samples and undoped monodomain LiNbO 3 , TGS, Gd 2 ͑MoO 4 ͒ 3 , and Pb 5 Ge 3 O 11 crystals were studied in the experiments.…”
Section: Fee During Phase Transitionsmentioning
confidence: 94%
“…Studies of the FEE effect in doped TGS crystals at low temperature showed that persistent electron emission is observed in the ferroelectric phase. 57 Estimations, fulfilled in the work by Rosenman et al, 57 showed that near the Curie temperature the relaxation time is very high because of a sharp growth of the dielectric permittivity . The results allowed one to simplify Eq.…”
Section: Fee During Phase Transitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a voluminous literature on electron emission and production phenomena [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and plasma [22][23][24][25] formation at the surface of pyroelectric and ferroelectrics crystals. Reference 4, a recent comprehensive review article, is representative but does not suggest that pyroelectric crystals can produce focused, stable energetic electron beams capable of ionizing K electrons in high-Z materials and producing K x-rays.…”
mentioning
confidence: 99%